Cartographic historiography: a descriptive overview of the production of maps in different societies - Teódulo, José Mácio Ramalho (2023)
This essay aimed to present a brief descriptive overview of the relevance of cartographic production throughout history. It sought to reflect, in a non-exhaustive way, its contemporaneity and importance, translated through emblematic maps: its main characteristics, its communication and information process, its evolutionary stage and its families. Studying and understanding its role, over different periods, becomes relevant as it lists geopolitical, sociocultural, and formative issues. Historiography is justified by highlighting imperative elements that touched on territorial directions and defined routes for humanity. These theoretical/technical elements, which determined parameters and directions, laid the foundations for cartographic tools of the present time. The methodology was based on an exploratory study with a qualitative approach, based on authors in the area, such as: Brotton, Harley, Harley and Woodward, Raisz, among others. The writing was organized in a strictly non-linear way, arranged within a logical sequence of events. As a final consideration, since the subject man saw himself as a thinking being, in some period of humanity, he decided to outline his geographic territory. From this starting point, he structured, based on the representation of his space, a new way of expressing, dominating, controlling, and expanding his corporate environment.